1983
DOI: 10.1002/1520-6807(198310)20:4<510::aid-pits2310200420>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the acceptability of behavioral interventions used in classrooms

Abstract: This study examined components of teacher judgements that an intervention is either acceptable or unacceptable. A total of 180 preservice and student teachers were asked to evaluate the acceptability of six different interventions. The evaluations of acceptability were assessed using a 20-item rating scale. A factor analysis of the rating scale yielded one major dimension, a general acceptability factor, and four secondary dimensions of intervention acceptability: risk to the target child, amount of teacher ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
172
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(178 citation statements)
references
References 16 publications
5
172
0
1
Order By: Relevance
“…That is, philosophies about the effectiveness and appropriateness of interventions that teachers hold may influence the frequency and integrity with which interventions are implemented and used in the classroom, and thus influence the behavioural and educational outcomes for the affected students. Witt, Martens and Elliott (1984) looked at factors, including time involvement, intervention type and problem behaviour severity, in relation to how teachers rated treatment acceptability (Witt and Martens 1983). Timeconsuming treatments were viewed as least acceptable, except in cases of severe behavioural problems.…”
Section: The Relation Between Teacher Factors and Students Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, philosophies about the effectiveness and appropriateness of interventions that teachers hold may influence the frequency and integrity with which interventions are implemented and used in the classroom, and thus influence the behavioural and educational outcomes for the affected students. Witt, Martens and Elliott (1984) looked at factors, including time involvement, intervention type and problem behaviour severity, in relation to how teachers rated treatment acceptability (Witt and Martens 1983). Timeconsuming treatments were viewed as least acceptable, except in cases of severe behavioural problems.…”
Section: The Relation Between Teacher Factors and Students Outcomesmentioning
confidence: 99%
“…The authors suggested that teachers' involvement increases when children display severely inappropriate behaviours. Witt and Martens (1983) also found that intervention acceptability, as indicated by 180 preservice and students teachers, was related to time requirements and behaviour severity, but results were obtained with small samples, little variability, teachers without much (if any) classroom experience and no reported statistical tests, making interpretations difficult and limited. The researchers conducted a factor analysis to determine which factors contributed to teachers' evaluations of intervention acceptability.…”
Section: The Relation Between Teacher Factors and Students Outcomesmentioning
confidence: 99%
“…The measure for the students was adapted from the Children's Interven-tion Rating Profi le , which is a Likert-type scale that assesses the child's acceptability of the intervention procedure. The parents completed an adapted version of the Intervention Rating Profi le-15 (Witt & Martens, 1983). The IRP-15 is a reliable (Cronbach alpha = .98; Martens, Witt, Elliott, & Darveaux, 1985), 15-item, Likert-type scale that assesses the acceptability of intervention procedures.…”
Section: Materials and Assessment Proceduresmentioning
confidence: 99%
“…Witt and Martens (1983) found that the main component influencing intervention acceptability ratings is the perception of whether the intervention is to be helpful for a child and suitable for the mainstream classroom settings (Sherman et al, 2008). In fact, more traditional forms of behaviour management, such as negative behavioural sanctions and extensive verbal instructions have been found to be ineffective in managing ADHD students' behaviour (DuPaul & Weygandt, 2006), and some strategies have been found to be condescending and cause students to resent teachers and schools (Prosser, 2008).…”
Section: Introductionmentioning
confidence: 99%